A value-focused approach for establishing requirements' specification of commercial aircraft. (September 2014) - Zhang, Xinwei; Tong, Shurong; Eres, Hakki; Kossmann, Mario; Wang, Keqin
Although systems engineering processes and standards are widely used in aircraft development programs, traditional requirements' engineering practice for commercial aircraft does not explicitly address value perceptions and associated information. In this paper, a value-focused approach is proposed to promote a better understanding of customer-value perceptions and their derivation among different levels for value-based requirements engineering of commercial aircraft. The approach is a four-step process starting from initial customer statements to a customer-value model and leading to a system-value model with associated component-value models. A set of theories and methods are introduced in order to resolve different aspects of the approach regarding the appropriate understanding of customer-value perceptions and the establishment of the value-based requirements' specification. A case study is used to demonstrate the transformation of airlines' initial expectation statements into three types of value models. There are two significant benefits of this approach: (a) perceived customer value can be explicitly modeled, simulated, and derived into different levels of the system development and (b) the value model can be subsequently utilized reactively for design evaluations and proactively for design optimization to generate creative design alternatives.